Mineralogical Code in Russian Color Names - Yu. A. Griber (Научный диалог, 2021)
The results of a comprehensive study of color names derived from the names of colored stones in the system of color names of the modern Russian language are presented in the article. The research was conducted in 2018-2020 in two stages using the methods of content analysis and an online psycholinguistic experiment. At the first stage, the state of the semantic group of names of colored stones, potential objects-referents of color names, was assessed by analyzing four different groups of sources: specialized dictionaries of colored stones, dictionaries of color, individual author's dictionaries of color names and explanatory dictionaries of the modern Russian language. At the second stage, the state of the color terms formed from the names of colored stones in the active vocabulary of modern Russian speakers was investigated on the basis of data from an online psycholinguistic experiment, in which 2,457 people aged 16 to 95 took part. The results of a comparative analysis of the lists of colored stones-prototypes of color names in the passive and active dictionaries of the speakers of the modern Russian language are presented. The scope of denotation and the function of color names derived from the names of colored stones are considered. Particular attention is paid to the analysis of the derivative productivity of the names of referent objects of the studied class and the frequency of use of individual color names in the responses of Russian speakers with different socio-demographic characteristics (gender, age, professional experience).